USE OF MODERN TEACHING TECHNOLOGIES IN HIGHER EDUCATION INSTITUTIONS - Kuldashev Asror Makhmudovich (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract: In this article, the introduction of modern teaching technologies in higher education, the development of knowledge through them, the deepening and expansion of the content of the studied subjects, its rapid updating, the use of more effective teaching methods, as well as the education of each student The content of significantly expanding the possibilities of obtaining lim is highlighted.